2016
DOI: 10.1016/j.celrep.2016.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Increased 4E-BP1 Expression Protects against Diet-Induced Obesity and Insulin Resistance in Male Mice

Abstract: Summary Obesity is a major risk factor driving the global type II diabetes pandemic. Yet, the molecular factors linking obesity to disease remain to be elucidated. Gender differences are apparent in humans and also observed in murine models. Here we link these differences to expression of eukaryotic translation initiation factor 4E binding protein 1 (4E-BP1), which upon HFD becomes significantly reduced in skeletal muscle and adipose tissue of male, but not female mice. Strikingly, restoring 4E-BP1 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 43 publications
8
53
0
Order By: Relevance
“…Indeed, we previously reported that mice lacking both 4E-BP1 and 4E-BP2 were more sensitive to diet-induced obesity and insulin resistance [12], a phenotype which is in agreement with the observation that protein level of 4E-BP1 is reduced in tissues of high-fat diet (HFD) fed mice [20]. In contrast, enhanced 4E-BP1 activity in mouse protects against age-and diet-induced insulin resistance and metabolic rate decline [20,21]. Muscle-specific transgenic overexpression of a constitutively active form of 4E-BP1 in mice results in skeletal muscle fiber atrophy and attenuates physical performance.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Indeed, we previously reported that mice lacking both 4E-BP1 and 4E-BP2 were more sensitive to diet-induced obesity and insulin resistance [12], a phenotype which is in agreement with the observation that protein level of 4E-BP1 is reduced in tissues of high-fat diet (HFD) fed mice [20]. In contrast, enhanced 4E-BP1 activity in mouse protects against age-and diet-induced insulin resistance and metabolic rate decline [20,21]. Muscle-specific transgenic overexpression of a constitutively active form of 4E-BP1 in mice results in skeletal muscle fiber atrophy and attenuates physical performance.…”
Section: Introductionsupporting
confidence: 88%
“…4E‐BP proteins link mTORC1 activity and metabolism by regulating insulin sensitivity and adipogenesis . Indeed, we previously reported that mice lacking both 4E‐BP1 and 4E‐BP2 were more sensitive to diet‐induced obesity and insulin resistance , a phenotype which is in agreement with the observation that protein level of 4E‐BP1 is reduced in tissues of high‐fat diet (HFD) fed mice . In contrast, enhanced 4E‐BP1 activity in mouse protects against age‐ and diet‐induced insulin resistance and metabolic rate decline .…”
Section: Introductionsupporting
confidence: 83%
“…Conversely, global deletion of 4E‐BP1 and 4E‐BP2, which are negatively regulated by mTORC1, has the opposite metabolic phenotype to that of S6K1 −/− mice, with increased adiposity and sensitivity to diet‐induced obesity which eventually leads to insulin resistance (Le Bacquer et al, ). Consistent with these results, overexpression of 4E‐BP1 protects against HFD‐induced obesity and insulin resistance in male mice, whereas the overexpression of 4E‐BP1 does not provide any beneficial protection to HFD‐fed female mice (Tsai et al, ). Moreover, mice with ablation of Grb10 (Grb10 −/− ) in peripheral tissues (except brain) (Wang et al, ) or disrupted Grb10 genes (Grb10Δ2‐4 m/+ ) (Smith et al, ) have increased body weight but reduced adiposity, increased insulin sensitivity and glucose tolerance and enhanced insulin signaling in insulin‐target tissues such as skeletal muscle and fat.…”
Section: Skeletal Insulin Resistance Disrupts Whole‐body Glucose Homementioning
confidence: 60%
“…173,174 However, the specific molecular and physiological mechanisms by which rapamycin extends life span are difficult to examine in mammals; while it is clear that inhibition of S6K1 signaling extends life span, and that inhibition of translation downstream of 4E-BP1 is beneficial for metabolic health, the contribution of autophagy to the effects of rapamycin on mammalian longevity has not been examined in detail. [175][176][177] However, there is reason to believe that many of the beneficial effects of rapamycin on aging may be driven in part by increased autophagy.…”
Section: The Lysosome In Aging and Diseasementioning
confidence: 99%